2019
DOI: 10.1080/19336918.2019.1644857
|View full text |Cite
|
Sign up to set email alerts
|

Stable contacts of naïve CD4 T cells with migratory dendritic cells are ICAM-1-dependent but dispensable for proliferation in vivo

Abstract: It is unclear if naïve T cells require dendritic cell ICAMs to proliferate inside lymph nodes. To check if and when CD4 lymphocytes use ICAMs on migratory DCs, wild-type and ICAM-1 and 2 double knock out bone marrow-derived DCs pulsed with saturating levels of an OT-II transgene-specific ovalbumin-derived peptide were co-transferred into skin-draining lymph nodes. Intravital imaging of OT-II lymphocytes entering these lymph nodes revealed that ICAM-1 and −2 deficient migratory DCs formed fewer stable conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
(43 reference statements)
0
9
1
Order By: Relevance
“…Furthermore, we found no role for T-cell expressed ICAM-1 and ICAM-2 in triggering MOG aa35−55 induced T-cell activation, suggesting a precise and non-interchangeable relationship in the molecular interactions between APCs and T cells at the IS. Our observations are in apparent contrast with previous studies failing to identify a role for ICAM-1 and ICAM-2 on DCs in inducing T-cell proliferation (58,59). Discrepancies between these studies might be due to subtle differences in experimental setups, including use of different DC polarization protocols and the use of different T-cell subsets, which may result in different TCR-pMHC affinity, ultimately affecting induction of T-cell proliferation.…”
Section: Absence Of Icam-1 and Icam-2 In C57bl/6j Mice Reduces The Hocontrasting
confidence: 99%
“…Furthermore, we found no role for T-cell expressed ICAM-1 and ICAM-2 in triggering MOG aa35−55 induced T-cell activation, suggesting a precise and non-interchangeable relationship in the molecular interactions between APCs and T cells at the IS. Our observations are in apparent contrast with previous studies failing to identify a role for ICAM-1 and ICAM-2 on DCs in inducing T-cell proliferation (58,59). Discrepancies between these studies might be due to subtle differences in experimental setups, including use of different DC polarization protocols and the use of different T-cell subsets, which may result in different TCR-pMHC affinity, ultimately affecting induction of T-cell proliferation.…”
Section: Absence Of Icam-1 and Icam-2 In C57bl/6j Mice Reduces The Hocontrasting
confidence: 99%
“…Its pathogenesis primarily involves genetic, environmental, and immune components ( 42 ). MS is an inflammatory cascade triggered by autoreactive effector T cells and is associated with immune cells such as B cells, macrophages, and natural killer cells ( 43 46 ). It has been found that medullary EVs present in the cerebrospinal fluid are derived from microglia, and microglia will generate and release IL1-β and MHC-II, indicating that EVs secreted by reactive myeloid cells may trigger neuroinflammation and contribute to the rapid spread and presentation of antigens ( 47 ).…”
Section: Evs and Autoimmune Diseasesmentioning
confidence: 99%
“…However, these results have to be interpreted with care due to the severe homing defects of these T cells. In contrast, deletion of ICAM1 on lymph node-resident (Feigelson et al, 2018) and migratory DCs (Kozlovski et al, 2019) appears to have no effect on initial T cell activation and proliferation but is crucial for the development of immunological memory . To address these points, we performed hock co-injections of differently labelled and peptide-loaded wt and hem1-/-DCs, followed by intravenously injected labelled OT-II T cells.…”
Section: Resultsmentioning
confidence: 84%
“…Deletion of LFA-1 or talin in T cells leads to strong in vivo T cell proliferation defects ( Kandula and Abraham, 2004 ; Wernimont et al, 2011 ); however, these results have to be interpreted with care due to the severe homing defects of these T cells. In contrast, deletion of ICAM1 on lymph node–resident ( Feigelson et al, 2018 ) and migratory DCs ( Kozlovski et al, 2019 ) appears to have no effect on initial T cell activation and proliferation, but is crucial for the development of immunological memory ( Scholer et al, 2008 ). To address these points, we performed hock co-injections of differently labeled and peptide-loaded WT and hem1 −/− DCs, which were followed by i.v.…”
Section: Resultsmentioning
confidence: 99%